KARAKTERISTIK LACTATE THRESHOLD PADA ATLET TAEKWONDO DAERAH ISTIMEWA YOGYAKARTA SELAMA KOMPETISI - - Widiyanto; Awan Hariono; Devi Tirtawirya (Jurnal Penelitian Humaniora, 2014)
This study aimed at investigating the characteristics of lactate threshold in Taekwondo Yogyakarta Special Region athletes during competition. This research is a descriptive study conducted with survey techniques. Data was collected with a test that aims to understand how high levels of lactic acid in the blood of Yogyakarta Taekwondo athletes during competition. The sample used in this study is a DIY Taekwondo athletes who participate in Taekwondo championship. This study was conducted in September 2013 at Sports Hall the National Development University of Yogyakarta. In this research, statistical analysis by paired sample t-test. All statistical analyzes were performed with computer applications using serial program SPSS for Windows version 19, with a signi icance level of 5 %. Different test results on the measurement of lactic acid levels at 1, at 2, at 3, at 4, and 5 to show that an increase in blood lactic acid levels. While the results of different tests on the blood lactic acid levels at 6 measurements decrease. Highest levels of lactic acid produced in the measurement to 5 or in Round 3. Recovery with a time of 10 minutes after the match has not been enough to restore blood lactic acid levels in condition before the match or at rest